Aspek Kehidupan Sosial dalam Drama Korupsi Karya Norbertus Riantiarno: Kajian Sosiologi Sastra - Lastunna Umi Kulsum; Putri Amalia Dwi Pitasari; Dwi Susanto (Universitas Sebelas Maret, 2024)
The purpose of this research is to find the influence of the author's social background and identify the aspects of social life reflected in the drama Korupsi by Norbertus Riantiarno. Descriptive qualitative is the type of research used in this study. The data source used in this research is the drama Korupsi by Norbertus Riantiarno which was uploaded through the YouTube channel of Teater Koma in 2021. The drama Korupsi has a duration of 39 minutes 54 seconds. The data in this study is information (words, phrases, clauses or sentences) related to aspects of social life in the drama Korupsi by Norbertus Riantiarno which is the source of research data. The results of the research can be concluded that the content of N. Riantiarno's works, especially plays, has political reflections in it that represent various political interests. N. Riantiarno said that he wanted to create a political-social mirror. In addition, there are seven social aspects reflected in the drama Korupsi, namely: 1) concern about the persistence of corruption, 2) corruption is the cause of the country's destruction, 3) officials corrupt to live in luxury, 4) regional leaders with poor performance, 5) religion used as political material, 6) special taxes for the rich, and 7) human lifestyle that causes disease to come.